Petrophysical Analysis and Hydrocarbon Potential in Low Resistivity Sandstone Reservoirs in Kutai Basin, East Kalimantan - Astuti, Bernadeta S.; Pambudi, Setyo; Correia, Pascoal (Syntax Literate, 2025)
The low-resistivity sandstone reservoir in the Kutai Basin presents challenges in petrophysical evaluation and hydrocarbon exploration optimization. This study aims to analyze petrophysical characteristics, identify factors that cause low resistivity, and examine the potential of hydrocarbons in sandstone reservoirs. The method used is a quantitative approach with secondary data analysis in the form of well logs, rock core data, geological data, and seismic data. The analysis was carried out through lithological characterization, shaly sand evaluation, calculation of petrophysical parameters (porosity, permeability, water saturation, resistivity), and reservoir modeling. The results showed that the prospect formation was at a depth of 2,432–4,910 ft subsea with a net thickness of 3–36 ft, a porosity value of 0.125, Vclay 40%, and a Sw of 0.2. This data allows the calculation of OOIP (Original Oil in Place) as an estimate of hydrocarbon potential. The findings indicate that low resistivity is mainly influenced by clay content and water saturation, thus requiring a multi-log evaluation approach (density, neutron, sonic, gamma ray, and Rt) validated with core data. This research is expected to contribute to improving the accuracy of reserve assessment, exploration efficiency, and the development of low-resistivity reservoir interpretation technology.